Archäologie der westlichen Slawen : Siedlung, Wirtschaft und Gesellschaft im früh- und hochmittelalterlichen Ostmitteleuropa - Brather, Sebastian (W. de Gruyter, 2008)
The present volume provides an overview of the present state of knowledge of the archaeology of the Early and High Middle Ages. A comprehensive account is given of the most recent reinterpretations? dendrochronology, interpretations from cultural history and historical modelling. The main focus is on the history of culture, settlement, society and economy of the Western Slavs between the Elbe/Saale and the Vistula. Brief summaries of the historical framework and the history of 'Slavic Archaeology' contextualise these aspects. Access to many detailed questions is provided by a thematically arr.
Keywords: Slavs, Western -- Antiquities.; Europe, Eastern -- Antiquities, Slavic.; Europe, Central -- Antiquities, Slavic.; Archaeology, Medieval -- Europe, Eastern.; Archaeology, Medieval -- Europe, Central.; Excavations (Archaeology) -- Europe, Eastern.; Excavations (Archaeology) -- Europe, Central.; Europe de l'Est -- Antiquités slaves.; Archéologie médiévale -- Europe de l'Est.; Archéologie médiévale -- Europe centrale.; Fouilles (Archéologie) -- Europe de l'Est.; Fouilles (Archéologie) -- Europe centrale.; Europe centrale -- Antiquités slaves.; HISTORY -- Ancient -- General.; Archaeology, Medieval; Excavations (Archaeology); Slavs, Western -- Antiquities; Central Europe; Eastern Europe